Hyaluronan and Its Heavy Chain Modification in Asthma Severity and Experimental Asthma Exacerbation - Lauer, Mark E. (J Biol Chem, 2015)
Hyaluronan (HA) is a large (>1500 kDa) polysaccharide of the extracellular matrix that has been linked to severity and inflammation in asthma. During inflammation, HA becomes covalently modified with heavy chains (HC-HA) from inter-α-inhibitor (IαI), which functions to increase its avidity for leukocytes. Our murine model of allergic pulmonary inflammation suggested that HC-HA may contribute to inflammation, adversely effecting lower airway remodeling and asthma severity. Our objective was to characterize the levels of HA and HC-HA in asthmatic subjects and to correlate these levels with asthma severity. We determined the levels and distribution of HA and HC-HA (i) from asthmatic and control lung tissue, (ii) in bronchoalveolar lavage fluid obtained from non-severe and severe asthmatics and controls, and (iii) in serum and urine from atopic asthmatics after an experimental asthma exacerbation. HC-HA distribution was observed (i) in the thickened basement membrane of asthmatic lower airways, (ii) around smooth muscle cells of the asthmatic submucosa, and (iii) around reserve cells of the asthmatic epithelium. Patients with severe asthma had increased HA levels in bronchoalveolar lavage fluid that correlated with pulmonary function and nitric oxide levels, whereas HC-HA was only observed in a patient with non-severe asthma. After an experimental asthma exacerbation, serum HA was increased within 4 h after challenge and remained elevated through 5 days after challenge. Urine HA and HC-HA were not significantly different. These data implicate HA and HC-HA in the pathogenesis of asthma severity that may occur in part due to repetitive asthma exacerbations over the course of the disease.